1986
DOI: 10.1161/01.str.17.6.1220
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in regional cerebral metabolic rate of oxygen during human aging.

Abstract: To investigate changes in cerebral circulation and oxygen metabolism during aging, regional cerebral blood flow (rCBF), regional oxygen extraction fraction (rOEF), regional cerebral metabolic rate of oxygen (rCMRO2) and regional cerebral blood volume (rCBV) were measured using the 15O labelled gas inhalation technique and a multi-slice positron emission tomograph (PET) in 22 healthy volunteers, aged from 26 to 64 years old. The measurements were performed with subjects at rest, without sensory deprivation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
133
7
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(165 citation statements)
references
References 33 publications
24
133
7
1
Order By: Relevance
“…An absolute CBF value of 40.8 6 4.3 ml/100 g/min in global GM agrees quite well with early PET results, even the variability across brain regions is partly reproduced (5,6). However, these studies exhibit a coarse spatial resolution, and thus certainly suffer from considerable partial volume effects.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…An absolute CBF value of 40.8 6 4.3 ml/100 g/min in global GM agrees quite well with early PET results, even the variability across brain regions is partly reproduced (5,6). However, these studies exhibit a coarse spatial resolution, and thus certainly suffer from considerable partial volume effects.…”
Section: Discussionsupporting
confidence: 84%
“…CBF corr was significantly reduced in the right superior parietal cortex and precuneus as well as bilateral caudate. Previous studies without PVC but with regional information reported decreasing CBF with increasing age in frontal (5,12,23) and parietal areas (12,23), in the insular cortex (5,23), in the cingulate and parahippocampal cortex (23) as well as a trend in the caudate (6). Even though the imaging volume of our study (parallel to and comprising the hippocampus) did not comprise substantial portions of the frontal cortex, the ROI analysis without PVC revealed significant CBF reductions in inferior frontal and olfactory cortex, and the CBF in the cingulate cortex, the parahippocampus and the insula was somewhat lower in elderly subjects, although insignificantly.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Significant CMR O2 reduction and relatively constant CMR glc (i.e., a reduced oxygen-to-glucose index) in older people have been reported (36,37). Moreover, the notion that age-induced decrease in NAD + /NADH RX reflects deficiency in mitochondrial capacity for oxidative phosphorylation is also supported by significant decreases (e.g., 15-34%) in respiratory enzyme (complexes I-V) activities observed in aged mice brains (38), which is in line with another human brain study showing an ∌30% reduction in both neuronal oxidative glucose metabolism and neurotransmission cycling rates in elderly people (39).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3) and reasonable absolute values [31][32][33][34], a comparison between calibrated DSC-MRI and pCASL is indeed of interest. Nevertheless, it should be remembered that the value of M0 a scales all the CBF values in a pCASL volume, so the method used to determine M0 a will directly influence the absolute level of CBF.…”
Section: Comparison With Pcaslmentioning
confidence: 63%